Penerapan Bulding Information Modelling (BIM) Autodesk Revit dalam Pembuatan Bar Bending Schedule (BBS) Pondasi Pile Cap Proyek Apartemen Jkt Living Star - Jakarta Timur - Muhamad Alimin,; Imron Imron,; Muhammad Taulani, (JURAL RISET RUMPUN ILMU TEKNIK, 2023)
Bar bending schedule is a systeem of bending patterns of reinforcement that includes data on diameter, shape, length and number of reinforcement. The purpose of this study is to obtain images of bar bending schedule documents, pile cap foundation iron volumes and find out whether Autodesk Revit software is more efficient and effective than conventional methods. This research uses quantitative methods and the manufacturing process uses the concept of Building Information Modeling (BIM) with autodesk revit software. The results showed that the use of Autodesk Revit software makes it more effective, especially in making bar bending schedule documents, because everything is made automatically. The volume of pile cap iron produced by Autodesk Revit software is 46,878 kg has a difference with the existing (conventional) volume. The volume result of autodesk revit software is less with a difference of 1.29%. This shows that Autodesk Revit software is more efficient in terms of calculating the volume of concrete iron.